The Measurement of Language Lateralization with Functional Transcranial Doppler and Functional MRI: A Critical Evaluation - Somers, Metten; Neggers, Sebastiaan F.; Diederen, Kelly M.; Boks, Marco P.; Kahn, Rene S.; Sommer, Iris E. (Frontiers in Human Neuroscience, 2011)
Cerebral language lateralization can be assessed in several ways. In healthy subjects, functional MRI (fMRI) during performance of a language task has evolved to be the most frequently applied method. Functional transcranial Doppler (fTCD) may provide a valid alternative, but has been used rarely. Both techniques have their own strengths and weaknesses and as a result may be applied in different fields of research. Until now, only one relatively small study (n = 13) investigated the correlation between lateralization indices (LIs) measured by fTCD and fMRI and showed a remarkably high correlation. To further evaluate the correlation between LIs measured with fTCD and fMRI, we compared LIs of 22 healthy subjects (12 left- and 10 right-handed) using the same word generation paradigm for the fTCD as for the fMRI experiment. LIs measured with fTCD were highly but imperfectly correlated with LIs measured with fMRI (Spearman's rho = 0.75, p < 0.001). The imperfectness of the correlation can partially be explained by methodological restrictions of fMRI as well as fTCD. Our results suggest that fTCD can be a valid alternative for fMRI to measure lateralization, particularly when costs or mobility are important factors in the study design.